Service value co-creation in research & innovation practices in higher education institutions in Malaysia - Moses, Golooba; Ahlan, Abdul Rahman (Elsevier Ltd, 2013)
In today’s knowledge-based society, research and innovations play a critical role in social and economic transformation. However, the higher education institutions (HEIs), which are the main hubs for knowledge generation, usually produce basic research, yet innovations are mainly carried out by the industry. Therefore, this study explores the idea of value co-creation between HEIs and the Industry for purposes of increasing the volume and value of research. In this paper we propose a conceptual framework for service systems’ architecture which draws from the service dominant logic and work systems theories. The paper is conceptual however, it is hoped that if implemented can provide the participating entities with a platform to integrate and share resources for each ones benefit.